Origin of multiferroism in Sm2BaCuO5. (1st September 2022) - Apostolov, A.T.; Apostolova, I.N.; Wesselinowa, J.M.
Abstract: Proposing a microscopic model we have investigated the multiferroic properties of Sm 2 BaCuO 5 . The heat capacity shows two peaks at the antiferromagnetic transitions temperatures T N 1 ∼ 5 K and T N 2 ∼ 23 K. For the appearing of the extraordinary polarization Δ P in Sm 2 BaCuO 5 we have considered the single-ion magnetostriction mechanism. Δ P is zero without magnetic field. An external magnetic field h induces an electric polarization Δ P below T N 2 which varies linearly with h showing a linear magnetoelectric effect. Below T N 1 Δ P decreases due to ordering of the Sm-sublattice. There are some discrepancies in the experimental data for Δ P ( T, h ) which we will try to clarify. In addition, the temperature and magnetic field dependence of the dielectric constant is discussed. The observed maximum value of the peak at T N 2 shifts to smaller temperature values and increases with increasing external magnetic field. Highlights: The specific heat of multiferroic Sm2 BaCuO5 shows peaks at TN1 = 5 K and TN2 = 23 K. The observed polarization Δ P is due to the single-ion magnetostriction mechanism. A magnetic field h induces Δ P below TN2 which varies linearly with h. Below TN1 Δ P decreases due to ordering of the Sm-sublattice. The temperature and magnetic field dependence of the dielectric constant is also discussed.